2017
DOI: 10.1080/00016489.2017.1322712
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tonsillotomy on chronic recurrent tonsillitis in children

Abstract: Tonsillotomy is beneficial for patients with recurrent tonsillitis and carries less risk of postoperative complications than tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…20 While there are several reasons for this, one reason is to avoid surgery on children with the associated complications of ET including postoperative hemorrhage and pain. If IT in future studies continues to be shown to be effective in treating chronic tonsillitis as some studies have concluded already, 29,31 the indications for surgical treatment of chronic tonsillitis may expand.…”
Section: Paradigm Shift Implicationsmentioning
confidence: 99%
“…20 While there are several reasons for this, one reason is to avoid surgery on children with the associated complications of ET including postoperative hemorrhage and pain. If IT in future studies continues to be shown to be effective in treating chronic tonsillitis as some studies have concluded already, 29,31 the indications for surgical treatment of chronic tonsillitis may expand.…”
Section: Paradigm Shift Implicationsmentioning
confidence: 99%
“…Despite the merits of PIT, there was still concern about regrowth and reinfection after the procedure. One study has reported regrowth after PIT, especially in cases of acute tonsillitis [25]. The authors concluded that very young children with tonsillar tissues that are yet to reach the maximal size are at a greater risk of tonsil regrowth for a minimum of 4 weeks and up to 1 year postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been published in other studies [18][19][20], reflecting an increased awareness of upper airway obstruction. TT is mostly performed because of obstructive symptoms, although a few studies have shown that TT can be beneficial also for children and young adults with recurrent tonsillitis [21,22].…”
Section: Discussionmentioning
confidence: 99%